From financial lock-in to resilience reconstruction: Climate risk, internal capital markets and organizational resilience of high-carbon enterprises - Ning Wang; Fengjuan Wang; YiTian Li; Yang Yuan (PLoS ONE, 2026)
Amid the accelerating global decarbonization, the mechanisms through which climate risk erodes the organizational resilience of high-carbon enterprises remain underexplored. Drawing on the financial lock-in perspective, we compile a panel of Chinese A-share listed enterprises in high-carbon industries from 2008 to 2023. The measurement of climate risk is achieved through the utilisation of a text-based index, with the analysis being conducted via fixed-effects models and mediation tests. This approach is employed to trace the causal pathways and to examine the moderation of these pathways by internal capital markets. The empirical results reveal three principal findings: Firstly, climate risk triggers a dual-path financial lock-in effect through financing constraints and internal capital misallocation, collectively accounting for 85.17% of the total negative impact on organizational resilience. Secondly, internal capital markets demonstrate a paradoxical dual role: while active resource reallocation buffers short-term climate shocks, financialization spillovers among subsidiaries exacerbate long-term transition risks. Thirdly, heterogeneity analysis uncovers temporal dynamics — chronic climate risks impose more severe resilience erosion than transition or acute risks, with climate-induced shocks exerting disproportionately negative effects on long-term performance relative to short-term volatility. This study offers an innovative perspective on the dynamic mechanisms of financial lock-in in the context of climate risks, proposing actionable policy solutions including the establishment of a climate-adaptive financial system, the implementation of comprehensive supervision of internal capital allocation, and the establishment of an industry-wide collaborative governance platform. These findings advance both theoretical understanding and practical strategies for managing the low-carbon transition challenges of high-carbon enterprises.